2020
DOI: 10.1590/1984-3143-ar2020-0555
|View full text |Cite
|
Sign up to set email alerts
|

Cryptorchidism in free-living jaguar (Panthera onca): first case report

Abstract: Cryptorchidism is a genital alteration wherein one or both testicles fail to descend into the scrotum and has multifactorial causes. A free-range adult male was captured twice in the Pantanal of Nhecolândia to put a GPS collar and semen collection. Pharmacological semen collection, andrological examination and semen analysis were performed. At the first capture and during the andrological examination only the left testis was found, and the male qualified as cryptorchid. The penis had no penile spines at either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, the present study was the first in which detomidine was used for feline semen collection thru urethral catheterization. Medetomidine, however, is widely used for this purpose as it is known to promote the release of sperm into the urethra, allowing the semen to be collected by urethral catheterization (Araujo et al, 2020b;Araujo et al, 2018;Jorge-Neto et al, 2020b;Jorge Neto et al, 2019;Lueders et al, 2012;Prochowska et al, 2015;Silva et al, 2019;Silvatti et al, 2020;Zambelli et al, 2008). Thereby, this study aimed to assess whether detomidine had the same effect as medetomidine for semen collection in domestic cats.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study was the first in which detomidine was used for feline semen collection thru urethral catheterization. Medetomidine, however, is widely used for this purpose as it is known to promote the release of sperm into the urethra, allowing the semen to be collected by urethral catheterization (Araujo et al, 2020b;Araujo et al, 2018;Jorge-Neto et al, 2020b;Jorge Neto et al, 2019;Lueders et al, 2012;Prochowska et al, 2015;Silva et al, 2019;Silvatti et al, 2020;Zambelli et al, 2008). Thereby, this study aimed to assess whether detomidine had the same effect as medetomidine for semen collection in domestic cats.…”
Section: Discussionmentioning
confidence: 99%
“…Although electroejaculation is a well-established semen collection technique in mammals (Silva et al, 2004), the pharmacological semen collection technique has demonstrated higher efficiency in obtaining higher quality semen in several wild species, like wild and domestic felids (Araujo et al 2018Jeong et al, 2018;Jorge Neto et al, 2019;Jorge-Neto et al, 2020;Kheirkhah et al, 2017;Lueders et al, 2012;Silva, Ullony, et al, 2019;Zambelli, Prati, Cunto, Iacono, & Merlo, 2008), bear (Curry & Roth, 2016;Jeong et al, 2019) and even giant anteater . This study was performed before the description of the pharmacological collection technique in wild animals, being the electroejaculator at the time the best option for semen recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The testicular volume was measured using a caliper and applying the equation for an ellipsoid 4/3 × π × L/2 × B1/2 × B2/2, where L, B1, and B2 are the length and two breadths of the ellipsoid ( Harcourt et al, 1995 ), then subsequently converted to grams (1.046) ( Johnson et al, 1981 ). The relative testicular weight (RTW) was determined by dividing the total testes' weight by the body weight ( Jorge-Neto et al, 2020c ; Silva et al, 2022 ; Silvatti et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%